Natural gas saving and emissions decrease in public health care sector - a case study = Ograniczenie zużycia gazu ziemnego i redukcja emisji w sektorze zdrowia publicznego ? studium przypadku - Mierka, Otto; Variny, Miroslav; Skalíková, Ingrida; Sámel, Peter; Kizek, Ján; Súth, Róbert; Nagy, Karol (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
A study on natural gas saving and emissions decrease in the public health care sector is presented. The analyzed hospital complex belongs to the largest ones in Slovakia and uses both hot water and water steam for heating purposes. Visual steam system inspection revealed serious inefficiencies, including steam venting, missing pipelines insulation and obsolete steam sources with dysfunctional blow-down system.
Keywords: public buildings; health care sector; natural gas; emissions; heat loss; budynek użyteczności publicznej; gaz ziemny; emisja; straty ciepła